2021
DOI: 10.1136/bmjdrc-2020-001894
|View full text |Cite
|
Sign up to set email alerts
|

Serum galectin-3BP as a novel marker of obesity and metabolic syndrome in Chinese adolescents

Abstract: IntroductionChildhood obesity (OB) and metabolic syndrome (MetS) have become a worldwide health problem. Comparative proteomic approaches are widely used in human OB to analyze protein changes in blood plasma. The present study determined the galectin-3 binding protein (galectin-3BP) expression level in different weight categories and assessed the associations between galectin-3BP and OB and MetS.Research design and methodsThe current study included 932 Chinese adolescents 13–18 years of age. The biochemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Also, patients with severe obesity and elevated galectin-3 had >4-fold higher risk of developing heart failure. One of the studies conducted by Zhen et al (7), reported elevated expression of Galectin-3BP and positive correlation with obesity and MetS in 932 Chinese adolescents. On the other side Besma et al (21) obtained no statistically significant results regarding BMI among patients with type 2 diabetes mellitus regarding rs4644 genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, patients with severe obesity and elevated galectin-3 had >4-fold higher risk of developing heart failure. One of the studies conducted by Zhen et al (7), reported elevated expression of Galectin-3BP and positive correlation with obesity and MetS in 932 Chinese adolescents. On the other side Besma et al (21) obtained no statistically significant results regarding BMI among patients with type 2 diabetes mellitus regarding rs4644 genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have found a positive correlation of circulating galectin 3 serum levels in general population with higher risk of cardiovascular, renal diseases, high blood pressure as well as with higher values of serum lipids and obesity (6). Also, galactines promote preadipocytes maturation into the lipidloaded adipocyte, which might contribute to central obesity (7). Moreover, deletion of LGALS3 gene in mice have shown defectiveness in adipose tissue maturation, which was accompanied by increased body inflammation, higher glucose level and impaired insulin sensitivity (8).…”
Section: Introductionmentioning
confidence: 96%
“…A study investigating links between body mass index (BMI) and differential methylation through whole-blood methylation analysis identified a particularly robust association in men. This was localized to a specific CpG site near the Lgals3bp gene ( 121 ), a recognized marker for obesity and metabolic syndrome ( 122 ). Additionally, higher levels of Line-1 methylation, responsible for coding transposable elements, were detected in men using peripheral blood.…”
Section: Epigenetic Differencesmentioning
confidence: 99%
“…В других исследованиях была показана связь системы БТШ с обменом глюкокортикоидов, минералокортикоидов и гормонов репродуктивной системы [ Помимо самого галектина-3, интерес представляет исследование связывающего белка -Galectin3BP (Galectin 3 binding protein), проведенного китайскими исследователями Zhen S. et al, на выборке, состоящей из 932 подростков (12-18 лет). Авторами исследования была получена статистически значимая ассоциация повышенных концентраций Galectin3BP с развитием ожирения и метаболического синдрома [Zhen S., 2021].…”
Section: общая характеристика белков теплового шокаunclassified